The Influence of Self-Care Management on Blood Pressure Control in Hypertensive Patients: A Literature Review - Asseggaf, Syarifah Nurul Yanti Rizki Syahab; Zakiah, Mistika; Ulfah, Ridha; Putri, Triyana Harlia; Len, Jenny Firda; Qatrunnada, Aura (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Hypertension, often referred to as the "silent killer," is a chronic condition characterized by systolic blood pressure >/140 mmHg and diastolic blood pressure >/90 mmHg. It is a major contributor to cardiovascular morbidity and mortality. One key factor affecting blood pressure control is adherence to antihypertensive medication, which is closely linked to self-care management. Objective: This literature review aims to analyze the influence of self-care management on blood pressure control in patients with hypertension. Methods: An integrative literature review was conducted by collecting references from electronic databases. Six journal articles that met the inclusion criteria were analyzed using descriptive analysis techniques. Results: The review found a strong correlation between effective self-care management and improved blood pressure control. Various factors were identified as influencing self-care capacity, including age, duration of illness, presence of comorbidities, self-efficacy, perception, and health literacy. These factors play a critical role in determining a patient's ability to manage their condition. Conclusion: Self-care management is essential in supporting medication adherence and achieving blood pressure control in hypertensive patients. Both intrinsic and extrinsic factors contribute to the effectiveness of self-care strategies and should be considered in hypertension management programs